1995
DOI: 10.1164/ajrccm/151.3_pt_1.785
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Talc Pleurodesis Is Associated with Increased Pleural Fibrinolysis

Abstract: Diffuse pleural inflammation and fibrin deposition following the instillation of the sclerosing agent is considered necessary for a successful pleural symphysis. We hypothesized that an impairment in fibrin formation or an increased endopleural fibrinolysis would lead to failure of pleurodesis. To investigate changes in the pleural coagulation/fibrinolysis balance, we studied 75 consecutive patients who underwent thoracoscopy. Fifty-four of these patients with malignant pleural effusions and four with a benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Demonstration of failed talc pleurodesis was associated with increased pleural fibrinolysis [12]. Therefore, in the presence of diclofenac, both reduced levels of TGF-β and increased levels of fibrinolysis factor D-dimer and human tPA in the pleural fluid may explain the reduced effect on pleurodesis described 3 weeks after thoracoscopic pleural abrasion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of failed talc pleurodesis was associated with increased pleural fibrinolysis [12]. Therefore, in the presence of diclofenac, both reduced levels of TGF-β and increased levels of fibrinolysis factor D-dimer and human tPA in the pleural fluid may explain the reduced effect on pleurodesis described 3 weeks after thoracoscopic pleural abrasion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Panadero et al demonstrated that successful pleurodesis was associated with significant reduction of the fibrinolytic activity expressed as pleural fluid D-dimer concentration 1 day after the administration of powdered talc ( p < 0.001). Interestingly, pleural D-dimer level did not decrease in patients with treatment failure [74]. On the contrary, a significant increase in fibrinolysis was observed 3 h after intrapleural talc administration in those patients.…”
Section: Coagulation Cascadementioning
confidence: 99%
“…In this regard, we hypothesized a few years ago that either an impaired fibrin formation or an increase in endopleural fibrinolysis would lead to pleurodesis failure. Our group demonstrated that failure of talc pleurodesis is associated with an increased pleural fibrinolysis [10]. …”
Section: Mechanisms Involved In Pleurodesismentioning
confidence: 99%